Pengaruh Jenis dan Konsentrasi Bahan Nabati terhadap Perkembangan Aspergillus flavus pada Medium PDA dan Biji Kacang Tanah - Sumartini Sumartini; Eriyanto Yusnawan (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
An experiment aimed to obtain botanical fungicide and its concentration to inhibit the growth of Aspergillus flavus was done in the mycology laboratory, Indonesia Legume and Tuber Crops Research Institute, Malang on June–August 2003. Kancil and Mahesa varieties of groundnut,  A. flavus  fungus, garlic, onion and ginger were used in this experiment.  The effectiveness of botanical fungicide extracts to inhibit A. flavus on PDA was done by culturing A. flavus (5 mm diameter) in the petridish ( θ = 9 cm). This experiment was arranged in a factorial completely randomized design with 5 replications. Factor A was botanical fungicide extracts (garlic, onion, ginger, and sterile water) and factor B was botanical fungicide concentrations (10%, 15%, 20%, dan 25%). The level concentration of botanical fungicide extracts  were poured into Petridish containing PDA medium before culturing A. flavus. The growth diameter of A. flavus was measured as a parameter. A similar experiment for testing  the effectiveness of botanical fungicide extracts to inhibit A. flavus was also done on groundnut kernel.  It was arranged in completely randomized design factorial, 3 replications. Fifty groundnut kernels were dipped on botanical fungicide extract for 3 minutes, placed on plastic tray (30 x 24 x 5 cm3) and layered with wet tissue sterile before used. After botanical fungicide extracts on kernels were air dried, the kernels were inoculated with spore suspension (approximately 104 spore/ml). Disease intensity of A. flavus was measured as a parameter. The result showed that the garlic extract treatment was more effective than those of onion extract, ginger extract and without botanical fungicide. The growth rate of  colony diameter of  A. flavus on PDA medium were 0.15 cm, 3.88 cm, 2.59 cm, and 4.30 cm respectively. The used of garlic extract at a concentration 10% on PDA could inhibit colony diameter growth of A. flavus by 97% as compared to without botanical fungicide extract. The garlic extract treatment, onion extract, ginger extract and without botanical fungicide extract showed that disease intensity A. flavus on groundnut kernels were 13.21%, 22.00%, 20.74%, and 25.18% respectively. An effective concentration to inhibit A. flavus infection on groundnut kernels was achieved by using garlic extract 20%. The use of its extract could reduce 73% of disease intensity. This result was different from the treatment on PDA. This was due to the ability of A. flavus to degrade cell walls. This process takes time meanwhile much of botanical fungicides extract have evapoured.